Drought could promote the heartwood formation in Dalbergia odorifera by enhancing the transformation of starch to soluble sugars. Issue 1 (2nd January 2022) - Cui, Zhiyi; Yang, Zengjiang; Xu, Daping; Li, Xiaofei
ABSTRACT: The heartwood of Dalbergia odorifera T. Chen ( D. odorifera ) is highly valuable. It was speculated that drought could promote heartwood formation in D. odorifera . To test this hypothesis, we artificially simulated conditions of low and high soil moisture content and investigated whether D. odorifera trees living in habitats with contrasting soil water conditions display distinct heartwood formation. Besides, we performed a preliminary study to explore the possible mechanism of drought affecting heartwood formation in D. odorifera in terms of non-structural carbohydrates (NSC). Higher heartwood formation percentage and heartwood size were observed in drought-treated trees. The heartwood density of drought-treated trees was significantly greater than that of control and the oil content of heavy drought-treated heartwood was significantly higher than that of the other treatments. None of water treatments had a significant effect on the essential oil components of heartwood. Furthermore, the effects of water treatments on the total amount of NSC were very limited; however drought treatments enhanced the transformation of starch to soluble sugars compared to control. This study confirmed the hypothesis that drought could promote the heartwood formation in D. odorifera, not by changing the total amount of NSC but by changing the component proportion of NSC.